Opium May Affect Coronary Artery Disease by Inducing Inflammation but not through the Expression of CD9, CD36, and CD68. (December 2022) - Momeni-Moghaddam, Mohammad Amin; Asadikaram, Gholamreza; Masoumi, Mohammad; Sadeghi, Erfan; Akbari, Hamed; Abolhassani, Moslem; Farsinejad, Alireza; Khaleghi, Morteza; Nematollahi, Mohammad Hadi; Dabiri, Shahriar; Arababadi, Mohammad Kazemi
The molecular mechanisms of opium with regard to coronary artery disease (CAD) have not yet been determined. The aim of the present study was to evaluate the effect of opium on the expression of scavenger receptors including CD36, CD68, and CD9 tetraspanin in monocytes and the plasma levels of tumor necrosis factor alpha (TNF-α), interferon gamma (IFN-γ), malondialdehyde (MDA), and nitric oxide metabolites (NOx ) in patients with CAD with and without opium addiction. This case-control study was conducted in three groups: (1) opium-addicted patients with CAD (CAD+OA, n=30); (2) patients with CAD with no opium addiction (CAD, n=30); and (3) individuals without CAD and opium addiction as the control group (Ctrl, n=17). Protein and messenger RNA (mRNA) levels of CD9, CD36, and CD68 were evaluated by flow cytometry and reverse transcription-quantitative PCR methods, respectively. Consumption of atorvastatin, aspirin, and glyceryl trinitrate was found to be higher in the CAD groups compared with the control group. The plasma level of TNF-α was significantly higher in the CAD+OA group than in the CAD and Ctrl groups (p=0.001 and p=0.005, respectively). MDA levels significantly increased in the CAD and CAD+OA groups in comparison with the Ctrl group (p=0.010 and p=0.002, respectively). No significant differences were found in CD9, CD36, CD68, IFN-γ, and NOx between the three groups. The findings demonstrated that opium did not have a significant effect on the expression of CD36, CD68, and CD9 at the gene and protein levels, but it might be involved in the development of CAD by inducing inflammation through other mechanisms.